EXTENSION OF THICKENED AND HOT LITHOSPHERES: INFERENCES FROM LABORATORY MODELING - Tirel C.; Brun J.-P.; Sokoutis D. (My University, 2006)
The extension of a previously thickened lithosphere is studied through a series of analogue experiments. The models deformed in free and boundary-controlled gravity spreading conditions that simulate the development of wide rift-type and core complex-type structures. In models, the development of structures mainly depends on boundary velocity and therefore on bulk strain rate. Wide rifts are of tilted block-type at high strain rate and of horst- and graben-type at low strain rate. The development of metamorphic core complex-type structures is enhanced by low strain rates and by the presence of weak heterogeneities within the ductile crust. Core complexes result from a necking instability of the upper crust creating a graben, which further widens, allowing the rise and exhumation of a ductile layer dome. An upward convex detachment, flat on top of the dome and steeper on dome limb, appears not to be the primary cause of the core complex development but its consequence.